COMPOSIÇÃO E DISTRIBUIÇÃO ESPAÇO-TEMPORAL DE POLYCHAETA PLANCTÔNICOS NO COMPLEXO ESTUARINO DE PARANAGUÁ, PARANÁ, BRASIL (25°S) - SANTOS, Marcos Eduardo Miranda (2019)
The Paranaguá Estuarine Complex (PES) is located on the northern limit of the coast of Paraná, southern Brazil. It is characterized by a relatively well-developed Maximum Turbidity Zone (MTZ) that concentrates between the Gererês Islands and the Port of Paranaguá. Assuming that the high nutrient concentrations in Paranaguá Bay and MTZ favor the aggregation of planktonic Polychaeta, we aimed to describe the spatial and seasonal variations of Polychaeta and their relationship with hydrography and food availability in the region. Polychaeta's density was analyzed from 74 zooplankton samples obtained from seasonal campaigns in winter 2013 and summer 2014. Fourteen taxa were sampled, classified into four categories: larvae, silid epitokes, juveniles and adults of typically benthic species. The highest densities were Chrysopetalum sp. (0.5 ± 1.76 ind.m-³), Spiophanes bombyx (1.3 ± 4.6 ind.m-³) Nereididae (3.68 ± 5.92 ind.m-³), Sabellaria wilsoni (3.57 ± 6.08 ind.m-³), Dysponetus sp. (2.09 ± 1.54 ind.m-³). Meroplanktonic polychaeta were dominant. The highest density values were recorded in summer and outside the estuarine complex. However, the diversity was higher in winter, being influenced by the influx of marine species in the internal sectors of the estuary. Community dynamics coincide with seasonal and spatial changes in the salinity level of the estuary. We highlight the occurrence of several benthic taxa suspended in the water column, probably due to disturbances of substrate suspension. We emphasize the importance of studies to understand the seasonal behavior of meroplanktonic larvae from the ecological and economic point of view, in order to assist future management projects by determining the breeding season, fertility and abundance.